4y-(2y-9)=2y-(-3y)-3

Simple and best practice solution for 4y-(2y-9)=2y-(-3y)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y-(2y-9)=2y-(-3y)-3 equation:



4y-(2y-9)=2y-(-3y)-3
We move all terms to the left:
4y-(2y-9)-(2y-(-3y)-3)=0
We get rid of parentheses
4y-2y-(2y-(-3y)-3)+9=0
We calculate terms in parentheses: -(2y-(-3y)-3), so:
2y-(-3y)-3
We get rid of parentheses
2y+3y-3
We add all the numbers together, and all the variables
5y-3
Back to the equation:
-(5y-3)
We add all the numbers together, and all the variables
2y-(5y-3)+9=0
We get rid of parentheses
2y-5y+3+9=0
We add all the numbers together, and all the variables
-3y+12=0
We move all terms containing y to the left, all other terms to the right
-3y=-12
y=-12/-3
y=+4

See similar equations:

| m-2/7=2 | | -3(3x+2)=-9x+2 | | -26=k-6 | | q-3.9=1.1 | | p+5=-1.9 | | (5–k)+2(-3k+4=) | | -4+b=16 | | z−8=10 | | -15+v=-22 | | 2^{7x}*8=256^x | | 5.4x−7.3=14.3 | | a+3a/2=15 | | 20x-2=103 | | 2/(x)=5 | | 2x-1=2x-15 | | x^2+16x-145=10x−7 | | -15+k=-26 | | 10-2(n-5)=10-4n | | -31=v-15 | | -(6n-1)=6n+3 | | 3x2−300=0 | | h/3+2/4=3(h+2)/12 | | 4+14x+20x-5+94+97=360 | | 3.5(2,25+x)=14 | | 29=y/24 | | 21x=8x-4(5-2x) | | h=4-5 | | 6=f/29 | | -18+k=-1 | | -5g=355 | | 25=y/31 | | 2|3x-6|+10=4 |

Equations solver categories